Analisis Keterbacaan Buku “Sabar” Menggunakan Teori Fog Index - Novianto, Syam Anis; Abdurrahman, Maman; Supriadi, Rinaldi (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2024)
One of the learning resources used in the learning process at school is instructional books or textbooks. The difficulties in textbooks will be felt by students as textbook users if the language aspects used in the book are quite complicated or difficult. So this research aims to discuss the readability level of discourse in an Arabic language textbook for class X SMA/SMK semester 1 based on the Fog Index readability formula. The method used is descriptive qualitative. Data was collected using documentation techniques and questionnaires regarding the discourse in the book. This research begins with defining textbooks and their readability, then analyzing the readability level of three discourses in the book